NARROW AND CONTRAST RESONANCE OF INCREASED ABSORPTION IN -SYSTEM OBSERVED IN Rb CELL WITH BUFFER GAS - A. Sargsyan; A. Papoyan; A. Sarkisyan; Yu. Malakyan; G. Grigoryan; D. Sarkisyan
We report observation of a narrow (sub-natural) and high-contrast resonance of increased absorption (“bright” resonance) in Rb cell with Ne buffer gas under previously unexplored experimental conditions for coupling and probe radiation configuration. The coupling laser-stabilized frequency is detuned by ~3 GHz from 5S1/2, Fg=3 - > 5P3/2, Fe=2,3,4 transitions, while the probe laser frequency is scanned across these transitions. We believe the bright resonance formation, occurring when the probe laser frequency is blue-shifted from the coupling frequency by a value of the ground state hyperfine splitting, is caused predominantly by a 2-photon absorption of the probe radiation 5S1/2, Fg=2 - > 5S1/2, Fg=3 with 5P3/2 as an intermediate state. We also report and interpret splitting of the bright resonance into 6 well resolved and contrast components in moderate magnetic fields (B ~ 10 - 250 G).
Keywords: Physics; Optics